1975
DOI: 10.3109/00498257509056120
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Benzpyrene Hydroxylase from Human Liver and Comparison with the Rat, Rabbit and Guinea-pig Enzymes

Abstract: 1. Benzpyrene hydroxylase of human liver biopsies and of livers from four inbred rat strains and from a non-inbred Sprague-Dawley rat strain, rabbit and guinea-pig was studied. 2. The human liver benzpyrene hydroxylase was similar to that of laboratory animals with respect to cofactor requirements, NADPH and O2, microsomal localization and inhibition by CO and N2. 3. Kinetic analysis of human adult benzpyrene hydroxylase indicated the presence of two enzymes, whereas human foetal liver contained only one enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…see Pelkonen, 1976;Pelkonen et al, 1984;Vahakangas et al, 1983). The few available studies with human tissues have not yielded definitive results (Boobis et al, 1980;Pelkonen et al, 1975;Vahakangas et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…see Pelkonen, 1976;Pelkonen et al, 1984;Vahakangas et al, 1983). The few available studies with human tissues have not yielded definitive results (Boobis et al, 1980;Pelkonen et al, 1975;Vahakangas et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sabadie et al (1980) demonstrated that the ability of human liver to catalyse the formation of mutagenic metabolites from N-nitroso-N'-methylpiperazine, presumably P-450-catalyzed reaction, was much higher than that of rodent livers. However, a general opinion has been, that human hepatic P-450-linked monooxygenase activities are lower than those in rodent livers (Kuntzman et al, 1966;Nelson et al, 1971;Ackerman, 1972;Pelkonen et al, 1975Pelkonen et al, , 1977Boobis et al, 1980;von Bahr et al, 1980;Jakobsson et al, 1982). Possible explanations can be sought from two directions.…”
Section: Discussionmentioning
confidence: 99%
“…There are indications that aryl hydrocarbon hydroxylase activity in liver biopsy samples from smokers is higher than that from nonsmokers (31). However, preferential inhibition of the hydroxylase in vitro shows (29) that the enzyme in human liver more closely resembles the control P450-associated enzyme in rat or mouse liver microsomes.…”
Section: Bp Metabolites Which Bind To Dna Generated By Human Liver MImentioning
confidence: 97%